The lithic microbial ecosystems of Antarctica’s McMurdo Dry Valleys - Ríos, Asunción de los; Wierzchos, Jacek; Ascaso, Carmen (Antarctic Science, 2014)
Received April 18 2013, Accepted March 07 2014, Online publication July 07 2014 We review the lithic microbial ecosystems of the McMurdo Dry Valleys as the main form of terrestrial colonization in this region, and assess the role of environmental controls such as temperature, solar radiation, water availability, wind, nutrient availability, salinity and the physicochemical properties of the colonized rock. Epilithic communities, especially those dominated by lichens, are able to withstand extreme environmental conditions but subsurface endolithic microhabitats provide more tolerant conditions. Endolithic microbial communities can be grouped into two main classes: eukaryotic communities (dominated by lichenized fungi and algae) and prokaryotic communities (dominated by cyanobacteria). Heterotrophic bacteria and non-lichenized algae and fungi (mainly black fungi) are also components of these communities. These lithobiontic microorganisms generally have effective mechanisms against freezing temperatures and desiccation. Extracellular polymeric substances play an important role not only in protecting microbial cells but also in community organization and in mitigating microenvironmental conditions. Antarctic lithobiontic communities are comprised of microbial consortia within which multiple interactions between the different biological and abiotic components are essential for microbial survival, whilst fossils and biomarkers provide evidence of earlier successful microbial life in Antarctic deserts. Finally, the uniqueness of the present lithobiont assemblages suggests they are the outcome of geographical isolation during the evolution of the continent and not merely the descendants of a subset of globally distributed taxa that have adapted to the extreme environmental conditions. This work was supported by grant CTM2012-38222-CO2-02 and CGL2010-16004 from the Spanish Ministry of Economy and Competitiveness. Peer reviewed